PENERAPAN STANDAR USAHA RUMAH MAKAN DIKAWASAN OBJEK WISATA PANTAI GANDORIAH PARIAMAN - Febrianti, Riri; Waryono, Waryono; Ferdian, Feri (Journal of Home Economics and Tourism, 2017)
The purpose of research is to know the standard business restaurant imp-lementation in the area of attractions Gandoriah Pariaman Beach.This research consists of two indicators are: product and service. This type of research is descriptive research using kualitatif data and kuantitatif data. Determination the research with the informant of purposive sampling is 7 restaurant owner.Data collection through interview, documentation and observation.Technic analysis data with reduction data, presentation data and conclusion.Based on the results of the study concluded that in general thestandard effort restaurant implementation about product in the form of spacious room of appropriate seating capacity, sufficient lighting and air circulation, food has been available, a clear sign is already applied. Food storage according hygiene sanitation applied 57,14%, restroom are clean and well maintained 14,28%, tables, chair and tableware according hygiene applied 57,14%, list menu accompanied price applied 57,14%. For service, serving meals are served by employees, payment is made by direct payment with respect to paying visitors and handling guest complaint by way of explaining to guest.Key Word: Implementation, Business Standar Restaurant1Prodi D4